Phase and stress evolution of Si swarf in the diamond-coated wire sawing of Si ingots. Issue 1 (March 2017) - Banerjee, Sriya; Yang, Junting; Wu, Junnan; Heredia, Michelle; Gao, Zhengning; Myung, Yoon; Rezvanian, Omid; Banerjee, Parag
Abstract Diamond-coated wire (DCW) sawing of Si solar ingots generates swarf which is analyzed using micro-Raman spectroscopy. Two types of Si swarf are found. Particulate swarf is crystalline and shows residual compressive stress. Fibrillar swarf is amorphous and shows residual tensile stress. The origin of particulate, crystalline swarf is attributed to brittle machining, while the origin of fibrillar, amorphous swarf is attributed to ductile machining. Finite element modeling suggests that brittle machining resulting in particulate, crystalline swarf generation is initiated by sharp diamond microparticles. On the other hand, ductile machining resulting in fibrillar, amorphous swarf generation is caused by blunt diamond microparticles. Over the course of sawing, the ratio of crystalline/amorphous phase in swarf decreases, quantifying the average loss in sharpness of diamond microparticles. Thus, micro-Raman spectroscopy can be an effective analytical tool for quantifying and monitoring DCW sawing processes for Si solar ingots.